Navigating Uncharted Territory: Exploring the Drivers and Challenges of TCFD Reporting in South Africa - Vermaas, Rupert (Graduate School of Business (GSB), 2025)
Climate-related risks and opportunities have a significant impact on companies' financial prospects. Publishing reports aligned with the Task Force on Climate-related Financial Disclosures (TCFD) recommendations plays a crucial role in aiding investor decision-making by ensuring that companies assess and provide fair presentation of material climate-related risks and opportunities. Understanding the drivers and challenges of TCFD reporting is vital to promoting its widespread adoption. However, there is a notable dearth of studies investigating the drivers and challenges of sustainability reporting in general, and TCFD reporting specifically, within the context of emerging markets like South Africa. Therefore, the objective of this study is to explore the drivers and challenges of TCFD reporting in South Africa by employing the legitimacy and stakeholder theories as a lens for analysis. The study used the conceptual model of influences around integrated reporting as a framework to answer the research question. This exploratory study employed a qualitative research approach by using semi-structured interviews to collect data from 7 experienced report preparers in South Africa. The findings indicate that TCFD reporting in South Africa is driven by institutional investors, activist shareholders, public commitments, competitors, and working groups that provide a collaborative space for knowledge sharing and skills development. Additionally, the study identifies data collection, cost and time, skills, confidentiality and security, scenario analysis, and greenwashing as significant challenges related to TCFD reporting. The findings of this study carry significant importance as they contribute to the literature on the drivers and challenges of climate-related disclosures in South Africa and other comparable emerging markets. Moreover, the adapted conceptual model developed in this study paves the way for exploring additional research questions on TCFD reporting. In addition to enriching the academic understanding, this study intends to provide valuable practical recommendations for policymakers and report preparers to encourage greater adoption of TCFD reporting in South Africa